Substitution and torsional effects on the energetics of homolytic N–H bond cleavage in diphenylamines. (April 2015) - Poliak, Peter; Vagánek, Adam; Lukeš, Vladimír; Klein, Erik
Abstract: The systematic study of substituent effects and torsional deformation on the N–H bond dissociation enthalpies (BDE) in diphenylamine (DPA) and 33 mono-, 33 di- and 22 tetrasubstituted diphenylamines is presented. The DPA and its derivatives were studied by means of (U)B3LYP/6-311++G** quantum-chemical method. Calculated gas-phase bond dissociation enthalpies approximated from the total electronic energies are in very good agreement with available experimental solution-phase data. The substitution in the ortho and para position(s) can considerably alter the N–H BDE. The largest N–H BDE decrease is caused by the hydrogen bond forming substituents (–OH, –NH2 ) in the ortho positions and strong electron-donating groups placed in the para positions. Therefore, the improvement of the DPA antioxidant effectiveness, i.e. N–H BDE decrease, can be accomplished by the substitution in ortho or para position(s). The changes in mutual aromatic rings orientation in DPA molecule and studied derivatives affect the N–H BDE values considerably (increase by up to 28 kJ mol −1 ). Hence, the mutual aromatic rings orientation alterations may induce negative effect on the antioxidant ability of DPA based antioxidants. Presented results indicate that the deviations of the antioxidant activity in various solid-phase matrices could have origin also in the mutual benzene ring orientation of the antioxidant molecule.